An approach to process parameter optimisation for beta titanium alloys - Rudolph Sabrina Mary-Ann; Dicks James Anthony; Becker Thorsten Hermann (MATEC Web of Conferences)
This study examined the influence of process parameters on porosity and mechanical properties in Laser Powder Bed Fusion (LPBF) of Beta 21S (Ti–15Mo–3Nb–3Al–0.2Si) and Ti5553 (Ti-5Al-5V-5Mo-3Cr) titanium alloys, with Ti64 (Ti-6Al-4V) as the reference material. Using the volumetric energy density – a function of laser power, scan speed, hatch spacing, and layer thickness – to inform the design space, a means to achieve optimal process parameters which minimise porosity content was explored. By employing a constrained design space and response surface methodology, windows of process parameters were identified. Regression models developed for predicting porosity achieved R-squared values of 0.822 for Ti64, 0.859 for Beta 21S, and 0.788 for Ti5553, indicating strong data fit. The model for Ti64 was validated against five literature sources, with four predictions falling within confidence bands and showing an error range of 0.07 to 0.48%. For Beta 21S and Ti5553, the combined error range for validation samples was 0.24 to 0.45%. Optimal volumetric energy density parameters were suggested to maximise relative density. Vickers hardness was assessed and compared favourably to existing literature. Significant variation was found amongst hardness data, suggesting that LPBF parameters influence mechanical performance. Further investigation is recommended to understand the effects of thermal history on the observed hardness behaviour.